Stereotactic Radiosurgery Compared With Active Surveillance for Asymptomatic, Parafalcine, and Parasagittal Meningiomas: A Matched Cohort Analysis From the IMPASSE Study. Issue 6 (25th June 2022) - Pikis, Stylianos; Mantziaris, Georgios; Bunevicius, Adomas; Islim, Abdurrahman I.; Peker, Selcuk; Samanci, Yavuz; Nabeel, Ahmed M.; Reda, Wael A.; Tawadros, Sameh R.; El-Shehaby, Amr M. N.; Abdelkarim, Khaled; Emad, Reem M.; et al.
Abstract : BACKGROUND: The optimal management of asymptomatic, presumed WHO grade I meningiomas remains controversial. OBJECTIVE: To define the safety and efficacy of stereotactic radiosurgery (SRS) compared with active surveillance for the management of patients with asymptomatic parafalcine/parasagittal (PFPS) meningiomas. METHODS: Data from SRS-treated patients from 14 centers and patients managed conservatively for an asymptomatic, PFPS meningioma were compared. Local tumor control rate and new neurological deficits development were evaluated in the active surveillance and the SRS-treated cohorts. RESULTS: There were 173 SRS-treated patients and 98 patients managed conservatively in the unmatched cohorts. After matching for patient age and tumor volume, there were 98 patients in each cohort. The median radiological follow-up period was 43 months for the SRS cohort and 36 months for the active surveillance cohort ( P = .04). The median clinical follow-up for the SRS and active surveillance cohorts were 44 and 36 months, respectively. Meningioma control was noted in all SRS-treated patients and in 61.2% of patients managed with active surveillance ( P < .001). SRS-related neurological deficits occurred in 3.1% of the patients (n = 3), which were all transient. In the active surveillance cohort, 2% of patients (n = 2) developed neurological symptoms because of tumor progression ( P = 1.0), resulting in death of 1 patient (1%). CONCLUSION: Up-front SRS affords superior radiological PFPS meningioma control as compared with active surveillance and may lower the risk of meningioma-related permanent neurological deficit and/or death. Abstract :